Impact of country’s governance dimensions on bank revenue efficiency: overview on middle east, Southeast Asia, and South Asia countries - Hussain, Hafezali Iqbal; Kamarudin, Fakarudin; Mohamad Anwar, Nazratul Aina; Md. Nassir, Annuar; Sufian, Fadzlan; Tan, Khar Mang (Vilnius University Press, 2020)
This study attempts to discover the impact of the limitation of a country’s governance on Islamic and conventional bank revenue efficiency by using data from the countries of three regions. Non-parametric Data Envelopment Analysis (DEA) employed to measure the bank revenue efficiency level. The applied method of estimation consists of pooled Ordinary Least Square (OLS), Fixed Effect Model (FEM), Random Effect Model (REM), and the Generalized Method of Moments (GMM) to examine the impact of country governance and other potential determinants on bank efficiency. This study finds out that the dimensions of voice and accountability positively influenced Islamic and conventional bank revenue efficiency, however, the political stability and absence of violence and control of corruption provided the negative relationship. Furthermore, other dimensions of regulatory quality, government effectiveness and rule of law significantly negative with the conventional bank revenue efficiency. Implications from the study allow the related parties to identify the significant dimensions of a country’s governance to the efficiency of the banks to ensure better bank performance.